Du monde réel au monde numérique - Abdelaziz Blilid; Laurence Favier (Communication)
In a very short amount of time, the Internet has helped the Amazighs do what they had been incapable of doing for many years: give shape to a new form of cultural activism, foster debate, articulate their demands, and facilitate contacts between different segments of the Amazigh population to establish an “imagined identity.” Facebook played a key role in the events that started in North Africa in 2011. The author analyzes links between Facebook pages that form a sort of “digital Amazigh community.” He used Netvizz, to compile a corpus of 2,259 pages that involve 14,136 connections.